Factors Negatively Affecting the Quality of Work of Pti Technicians - the Case of the Slovak Republic - Hudec, Juraj; Sarkan, Branislav (Communications - Scientific Letters of the University of Zilina, 2024)
The authors examine the negative impact of objective and subjective factors on the quality of work of periodical technical inspection stations (PTI) technicians. In this context, the authors conducted a survey among the PTI technicians and vehicle operators. From the results formulated in the article, it emerged that the quality of PTI technicians' work, and thus the entire PTI, is negatively affected mainly by the high degree of subjectivity entrusted to PTI technicians, when evaluating the technical condition of vehicles (94.12 %) and the resulting scope for incorrect judgments and influencing the result of PTI (corruption, acquaintances), and the approach of PTI owners (influencing technical inspections results due to fear of losing customers, pressure on quantity over quality, method of rewarding the PTI technicians, etc.). The authors also propose some measures to improve the quality of PTI activities.
Keywords: periodical technical inspection station; PTI technician; quality of work; road traffic safety